"La Reine Coax" (G. Sand) et «Le Roi grenouille» ou comment repenser la féminité - Auraix-Jonchière, Pascale (Ondina - Ondine, 2018)
Grimm brothers’ « The Frog Prince » takes part to a rich intertextual dialogue which nourishes George Sand’s « La Reine Coax ». Most of all, it consists in a process of feminisation, the social and ideological goals of which we intend to highlight.Keywords: tale, feminine representation, illustration, dialogism, culturel patterns.